THE EXISTENCE AND SURVIVAL STAGE IN SMEs SUSTAINABILITY TRANSFORMATION - Sarah Febrina Yolanda; Melia Famiola (Universitas Nusa Cendana, 2023)
The purpose of this study is to explore SMEs’ proactive approach towards sustainability transformation, especially in the existence and the survival stage, what are the challenges and opportunities that come with each stage of a company's existence can help SMEs plan for their sustainability transformation in a way that is appropriate for their current stage of development. The interpretivism paradigm is used in this study. This research involves collecting qualitative data through the interview method. Cross-sectional data were collected from 10 Indonesian SMEs which implemented sustainable business practices through convenience sampling and snowball sampling. Based on the interview, it was generally analyzed the data through initial coding, axial coding, selective coding, and lastly, using the results proposition to make new conclusions and recommendations for the study. The case studies discussed in this research provide insights into the sustainability transformation of SMEs at different stages of development, from existence to survival. The cases illustrate various challenges, opportunities, and approaches that SMEs can use to integrate sustainable practices into their operations. There are several limitations including a limited scope, level of depth, generalizability, reliance on self-report by SMEs, and time-bond. But despite the limitations of these studies, this research provides insights that can help to inform future research on sustainable entrepreneurship, social innovation, and corporate social responsibility. Keywords: Sustainable Business Practices; Sustainability Transformation; SMEs; Growth Stage Model